Evaluation of Modified Dorsonasal Flap for Reconstruction of Dorsonasal Defect in Erbil - Elza Faiz Hanna; Sabir Osman Mustafa (Advanced Medical Journal)
Background and objectives: nasal reconstruction is challenging for plastic surgeons mainly because of its midfacial location and the relationship between convexities and concavities of nasal subunits that make it difficult to hide any contour deformity; as a result, proper planning of final scar location is crucial for a successful aesthetic outcome. The modified dorsal nasal flap is used for resurfacing nasal tip defects with respect to these nasal subunits. This paper evaluates the outcome of a modified dorsonasal flap for reconstruction of the dorsal nasal defects.